Technical Properties of Normal Concrete with Alum Additive - Prabowo Setiyawan (JACEE (Journal of Advanced Civil and Environmental Engineering), 2023)
Concrete is a widely used construction material due to its numerous advantages in terms of structural performance, cost-effectiveness, implementation, and maintenance. Compressive strength is a critical property that must be considered for concrete used as a structural component. This property can be influenced by various factors, including the addition of chemical substances to the concrete mix. Alum is commonly employed as a water clarifying agent. In concrete mixtures, alum decomposes into aluminium and trioxide sulfate compounds found in cement. Incorporating alum into concrete is expected to enhance the aluminium and cement content. This research aims to investigate the technical properties of normal concrete when supplemented with alum. The technical properties under consideration include slump value and compressive strength, with a fixed mix proportion of cement: sand: gravel = 1:2:3. Alum is added in proportions of 2%, 4%, 6%, and 8% by weight of cement in the concrete mix. The findings of this present study indicate that the highest compressive strength is achieved in concrete specimens with 2% alum addition by weight of cement, reaching 35.629 MPa, while the corresponding slump value is 7.75 cm